Helicobacter pylori Eradication Therapies in the Era of Increasing Antibiotic Resistance: A Paradigm Shift to Improved Efficacy - Sotirios D. Georgopoulos; Vasilios Papastergiou; Stylianos Karatapanis (Gastroenterology Research and Practice)
With the rising prevalence of antimicrobial resistance, the eradication rates of Helicobacter pylori (H. pylori) with standard treatments are decreasing to unacceptable levels (i.e., ≤80%) in most countries. After these disappointing results, several authorities have proposed that infection with H. pylori should be approached and treated as any other bacterial infectious disease. This implicates that clinicians should prescribe empirical treatments yielding a per protocol eradication of at least 90%. In recent years several treatments producing ≥90% cure rates have been proposed including sequential therapy, concomitant quadruple therapy, hybrid (dual-concomitant) therapy, and bismuth-containing quadruple therapy. These treatments are likely to represent the recommended first-line treatments in the near future. In the present paper, we are considering a series of critical issues regarding currently available means and approaches for the management of H. pylori infection. Clinical needs and realistic endpoints are taken into account. Furthermore, emerging strategies for the eradication of H. pylori and the existing evidence of their clinical validation and widespread applicability are discussed.